Factors Influencing Psychological Problems for Emergency Nurses in Facing Emergency Situations during the Covid-19 Pandemic - Rahmi Fitria; Nana Aldriana; Sri Wulandari; Eka Yuli Handayani; Andria Andria (Universitas Aisyah Pringsewu, 2021)
The emergence of COVID-19 is placing unforeseen pressure on the country's health care system and presenting various challenges for healthcare workers. Health care workers are at high risk of infection, while they have a large burden on clinical care and prevention of Covid-19 virus infection, including emergency room nurses. The emergency room nurse is one of the medical personnel who plays an important role in providing health services to patients. Several previous studies revealed that there were psychological problems experienced by emergency room nurses such as anxiety, work stress, fear, and depression. Therefore, it is necessary to conduct a study to find out what are the predictors of psychological problems for emergency room nurses in dealing with emergencies situation during the COVID-19 pandemic. This research is a correlational analytic study using a cross-sectional design involving 85 emergency room nurses who are members of the Indonesian Emergency and Disaster Nurses Association (HIPGABI Bali). The data collection process is carried out online to the respondents. The data were analyzed by Spearman-Rank test with a significance level of (0.05). The results of the study were that the majority of emergency room nurses had normal anxiety responses and moderate stress. The factors related to anxiety are the completeness of hospital facilities (p-value = 0.000) and the presence of comorbidities (p-value = 0.007), while the only factor related to stress was the completeness of hospital facilities (p-value = 0.050). This can be a consideration for hospital management and professional organizations to take strategic steps to prevent nurses' psychological problems.Munculnya COVID-19 memberikan tekanan yang tidak terduga pada sistem perawatan kesehatan negara dan menghadirkan berbagai tantangan bagi tenaga kesehatan. Petugas kesehatan sangat berisiko terinfeksi, sementara mereka memiliki beban yang besar dalam perawatan klinis dan pencegahan infeksi virus Covid-19, termasuk para perawat UGD. Perawat UGD merupakan salah satu tenaga medis yang berperan penting dalam memberikan pelayanan kesehatan terhadap pasien. Beberapa penelitian terdahulu mengungkapkan adanya masalah psikologis yang dialami oleh perawat UGD seperti ansietas, stress kerja, ketakutan, hingga depresi. Oleh karena itu perlu dilakukan sebuah penelitian untuk mengetahui apa saja yang menjadi faktor prediktor masalah psikologis perawat UGD dalam menghadapi situasi gawat darurat selama masa pandemic COVID-19. Penelitian yang dilakukan merupakan penelitian analitik korelasional dengan menggunakan rancangan potong lintang yang melibatkan 85 perawat UGD yang tergabung dalam Himpunan Perawat Gawat Darurat dan Bencana Indonesia (HIPGABI Bali). Proses pengumpulan data dilaksanakan secara online kepada responden. Data dianailisis dengan uji Spearman Rank dengan tingkat kemaknaan £ (0.05). Hasil penelitian mayoritas perawat UGD memiliki respon ansietas normal dan stress sedang. Adapun faktor yang berhubungan dengan ansietas adalah kelengkapan fasilitas RS (p value = 0.000). dan adanya komorbid (p value = 0.007)., sedangkan satu-satunya faktor yang berhubungan dengan stress adalah kelengkapan fasilitas RS (p value = 0.050). Hal ini dapat menjadi pertimbangan bagi pihak manajemen RS dan organisasi profesi untuk mengambil langkah-langkah strategis sebagai upaya pencegahan masalah psikologis perawat.